2019
DOI: 10.1016/j.tplants.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Protists: Puppet Masters of the Rhizosphere Microbiome

Abstract: The rhizosphere microbiome is a central determinant of plant performance. Microbiome assembly has traditionally been investigated from a bottom-up perspective, assessing how resources such as root exudates drive microbiome assembly. However, the importance of predation as a driver of microbiome structure has to date largely remained overlooked. Here we review the importance of protists, a paraphyletic group of unicellular eukaryotes, as a key regulator of microbiome assembly. Protists can promote plant-benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
209
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(253 citation statements)
references
References 109 publications
10
209
3
Order By: Relevance
“…These observations are consistent with previous plant microbiome studies considering oomycetes diversity, that always described Pythium as the most dominant taxa among oomycetes [38,40,41]. These results confirm that protists are an integral part of the plant holobiont and their roles in controlling microbial populations through predation, disease incidence or contribution to nutrient cycles through the microbial loop deserve more attention [13].…”
Section: Evidences For a Wheat Core Microbiome And Identification Of supporting
confidence: 92%
See 1 more Smart Citation
“…These observations are consistent with previous plant microbiome studies considering oomycetes diversity, that always described Pythium as the most dominant taxa among oomycetes [38,40,41]. These results confirm that protists are an integral part of the plant holobiont and their roles in controlling microbial populations through predation, disease incidence or contribution to nutrient cycles through the microbial loop deserve more attention [13].…”
Section: Evidences For a Wheat Core Microbiome And Identification Of supporting
confidence: 92%
“…amoeba, ciliates, stramenopiles) is currently available. Protists as predators, saprotrophs or phototrophs influence nutrient cycles in the rhizosphere and exert a strong top-down control on microbial (mainly bacterial) biomass and composition [13]. Still, despite protists high diversity and biomass in the rhizosphere, they represent an overlooked component of the plant holobiont.…”
Section: Introductionmentioning
confidence: 99%
“…The co-occurrence analysis of bacteria, fungi, and protozoa revealed complex networks with numerous positive and negative correlations, similar to those described in the rhizosphere of wild and managed V. angustifolium (Yurgel et al, 2018). Interestingly, our analysis also revealed that microbial communities of SHB, Vd, and Vg differ in the abundance of various predatory protists, which feed on bacteria and fungi and have recently emerged as a key factor that shapes the rhizosphere microbiome and selects for plant-beneficial functional traits (Gao et al, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…However, pathogen success and plant health are ultimately controlled by other biota, particularly the rhizosphere microbiome [3,4]. The plant rhizosphere microbiome is a complex assembly of diverse microorganisms, including bacteria, fungi, and protists that together influence plant health [5][6][7][8]. Despite the fact that the microbiome consists of diverse groups, most research aiming to understand the role of the microbiome in plant health or disease suppression has focused on bacteria [9][10][11] and fungi [12,13].…”
Section: Introductionmentioning
confidence: 99%